NMR structure of a non-conjugatable, ADP-ribosylation associated, ubiquitin-like domain from Tetrahymena thermophila polyubiquitin locus - Chiarini, Valerio; Tossavainen, Helena; Sharma, Vivek; Colotti, Gianni (Biochimica et biophysica acta. General subjects, 2019)
Ubiquitin-like domains (UbLs), in addition to being post-translationally conjugated to the target through the E1-E2-E3 enzymatic cascade, can be translated as a part of the protein they ought to regulate. As integral UbLs coexist with the rest of the protein, their structural properties can differ from canonical ubiquitin, depending on the protein context and how they interact with it. In this work, we investigate T.th-ubl5, a UbL present in a polyubiquitin locus of Tetrahymena thermophila, which is integral to an ADP-ribosyl transferase protein. Only one other co-occurrence of these two domains within the same protein has been reported. NMR, multiple sequence alignment, MD simulations and SPR have been used to characterize the structure of T.th-ubl5, identify putative binders and experimentally test the interaction, respectively. Molecular dynamics simulations showed that T.th-ubl5 is unable to bind the proteasome like ubiquitin due to the lack of the conserved hydrophobic patch. Of other integral UbLs identified by structural and sequence alignment, T.th-ubl5 showed high structural and sequence resemblance with the Ras-binding epitope of FERM UbLs. SPR experiments confirmed that a strong and specific interaction occurs between T.th-ubl5 and T.th-Ras. Data indicate that T.th-ubl5 does not interact with the proteasome like ubiquitin but acts as a decoy for the recruitment of Ras protein by the ADP-ribosyl transferase domain. Mono-ADP-ribosylation of Ras proteins is known as a prerogative of bacterial toxins. T.th-ubl5 mediated recruitment of Ras highlights the possibility of an unprecedented post-translational modification with interesting implication for signalling pathways. •Many proteins contain regulative domains featuring ubiquitin-like fold (UbL).•An unexampled case sees a UbL as part of an ADP-ribosylation domain protein.•Binding to proteasome is hampered by the lack of conserved hydrophobic patch.•UbL acts as decoying particle for Ras recruitment.